Analisis Manfaat Dan Pentingnya Perjanjian Perkawinan - Ni’mah, Alna Fadliah Ais Fatchun; Yunanto, Yunanto (Fakultas Syariah INSURI Ponorogo, 2023)
A marriage agreement is a form of agreement between husband and wife that binds both parties, both before marriage and after marriage. The Marriage Agreement is made to minimize and prevent disputes between husband and wife and to provide legal certainty between the rights and obligations of each party. From a societal point of view, the marriage covenant has a negative stigma against the marriage covenant, and many people question the importance of the marriage covenant in the family. This research uses normative juridical research methods, this research will be carried out by means of a Literature Study. The legal effect of a marriage agreement involving joint property is the separation of property. A marriage agreement that serves as a preventive measure in case of conflict in the future.